Reports - Filipenko, Volodymyr; Shevchenko, Olena; Klepach, Mykola; Smolynskyy, Oleksandr; Vasiuk, Volodymyr; Zinchenko, Anatoliy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Report on the work of societies and associations orthopedic trauma Ukraine.